Inhibition of colony-stimulating factor 1 receptor early in disease ameliorates motor deficits in SCA1 mice - Wenhui Qu (Journal of Neuroinflammation, 2017)
Abstract Background Polyglutamine (polyQ) expansion in the protein Ataxin-1 (ATXN1) causes spinocerebellar ataxia type 1 (SCA1), a fatal dominantly inherited neurodegenerative disease characterized by motor deficits, cerebellar neurodegeneration, and gliosis. Currently, there are no treatments available to delay or ameliorate SCA1. We have examined the effect of depleting microglia during the early stage of disease by using PLX, an inhibitor of colony-stimulating factor 1 receptor (CSFR1), on disease severity in a mouse model of SCA1. Methods Transgenic mouse model of SCA1, ATXN1[82Q] mice, and wild-type littermate controls were treated with PLX from 3 weeks of age. The effects of PLX on microglial density, astrogliosis, motor behavior, atrophy, and gene expression of Purkinje neurons were examined at 3 months of age. Results PLX treatment resulted in the elimination of 70–80% of microglia from the cerebellum of both wild-type and ATXN1[82Q] mice. Importantly, PLX ameliorated motor deficits in SCA1 mice. While we have not observed significant improvement in the atrophy or disease-associated gene expression changes in Purkinje neurons upon PLX treatment, we have detected reduced expression of pro-inflammatory cytokine tumor necrosis factor alpha (TNFα) and increase in the protein levels of wild-type ataxin-1 and post-synaptic density protein 95 (PSD95) that may help improve PN function. Conclusions A decrease in the number of microglia during an early stage of disease resulted in the amelioration of motor deficits in SCA1 mice.